Enhancing managerial performance through budget participation: insights from a two-stage A PLS-SEM and artificial neural network approach (ANN) - Alhasnawi, Mushtaq Yousif; Mohd Said, Ridzwana; Mat Daud, Zaidi; Muhammad, Haslinah (Multidisciplinary Digital Publishing Institute, 2023)
Including employees and stakeholders in the budgeting process enhances decision-making, encourages trust, and increases the probability of goal attainment. The present study investigates the simultaneous impact of motivational and cognitive variables of budget participation on managerial performance (MP). Based on goal-setting theory and the literature review, budget goal clarity and commitment have been determined as mediators in linking participation's motivational and cognitive effects on performance, with leadership style as a moderator variable in such interactions. Besides this, it also examined the significance and strength of the associations between budget participation, goal clarity and commitment, and managerial performance by using both PLS-SEM and ANN approaches. Questionnaires were used to obtain primary data from 373 Iraqi Higher education institution (HEIs) managers, with a response rate of 58.37 %. Statistical analysis was performed with PL S-SEM using SmartPLS 4.0, while SPSS was used to implement ANN. The results revealed that budget participation improves managerial performance by promoting goal clarity and commitment. Participative leadership amplifies the positive associations between budget participation and clarity and commitment. This study adds vision to the mediating roles of budget goal clarity and commitment and the moderating role of participative leadership, especially in developing countries such as Iraq. It also contributes to adding insights into the management accounting literature regarding a more complex process explaining the performance of employees generated by their participation in the budgeting process.